On the development of a professional mandate by social workers in medical rehabilitation– key results from the SWIMMER Project - Knoop, Tobias; Freymüller, Nadja; Dettmers, Stephan; Meyer-Feil, Thorsten (Frontiers in Rehabilitation Sciences, 2024)
Social work in the German rehabilitation sector is practiced with great variation and its interventions lack research evidence. The SWIMMER project aims to develop a program theory of social work in rehabilitation to explain this variation and to discuss possible conditions. The dealing with ethical dilemmas by social workers is one possible influence and the focus of this paper. The social workers’ practice was analyzed using the triple mandate, a German-Swiss concept that describes three possible, sometimes simultaneous directives without a concrete call to action from society, the client or the profession. This qualitative, case-comparative research project collected data from interviews with social workers and managers, participant observation and counseling sessions in ten German rehabilitation facilities. Social workers were confronted with all three mandates. They prioritized either the societal mandate or the client mandate. A consequence for social work practice was the limitation of options under social law (mandate by society). Social workers relied on their professional experience to reflect on the mandates. They used a variety of strategies when faced with conflicting mandates. The research project has succeeded in systematizing the orientations of social workers in goal conflicts. Further investigation on this topic on a broader basis would be beneficial.